Business Planning for Competitive Advantage: An Analysis of Potential and Challenges in the Shoe Care Service Industry - Sabilillah, Raehan Daffa; Jazuli, Muhamad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a major contribution to the Indonesian economy, including in the growing shoe washing service sector. In Malang Regency, this sector shows significant growth potential, especially with increasing demand in line with people's lifestyles that increasingly prioritize hygiene and shoe care. Data shows that the population in Malang Regency, the majority of whom are of productive age, has a high need for shoe care services, especially among students, students, and workers. However, despite the great opportunities, businesses like Rebel Shoescare face challenges in terms of marketing and brand recognition, especially with many competitors already present in the market. Therefore, this study aims to analyze the potential and challenges faced by the shoe washing business Rebel Shoescare in Malang Regency, as well as the importance of business planning to support the sustainability and growth of the business. This research is expected to provide a clear picture of the strategies that need to be implemented by business actors to face competition and optimize existing opportunities.